Radical Cystectomy With Urinary Diversion in the Form of Ileal Conduit : Outcome Analysis in 15 Cases Done by Single Surgeon - Biswas, Mrinmoy; Uddin, Sharif Mohammad Wasim; Sharifa, Jasmine; Ghosal, Sharmishtha; Khan, Mohammad Ohiduzzaman (Bangladesh Journal of Urology, 2020)
Objective: To analyse the outcome of 15 cases of radical cystectomy with urinarydiversion in the form of ileal conduit done by single surgeon. Methods: This retrospective study included 15 cases of radical cystectomy with urinarydiversion in the form of ileal conduit between 2014 and 2018 done by single surgeon indifferent hospitals. Follow up of these patients continued up to June 2018.Data werecollected through follow up visits at every 3 months interval in the first year, and then forevery 6 months from the second year. Results: In this study, the mean age was 67.67 years. Early complications like wounddehiscence, wound infection, bowel obstruction and GIT bleeding occurred in 47%patients and maximum were wound dehiscence (20%) and wound infection (13.3%).High incidence of early complications in this study may have multiple reasons likepreoperative co-morbidity, small sample size study and lastly surgeons learning curvebecause in early phase, complications occurred in 63% cases but only 29% cases inlate phase.Seven patients (46.7%) developed ED postoperatively. Recurrent UTI was recorded in33.3% cases. During mean 2.4 years follow up time, there was no local recurrence. Conclusions: Radical cystectomy for the muscle invasive urothelial bladder cancer isthe elective treatment and urinary diversion in the form of ileal conduit is a safe andconvenient option with less post operative complications and with good oncologicaloutcome. But for better evaluation of post operative outcomes, large sample size andlong term follow up are recommended. Bangladesh Journal of Urology, Vol. 22, No. 1, January 2019 p.63-68